Opioid Policy Changes During the COVID-19 Pandemic - and Beyond. Issue 4 (July 2020) - Davis, Corey S.; Samuels, Elizabeth A.
Abstract : N/A: The United States is currently in the midst of 2 public health emergencies: COVID-19 and the ongoing opioid crisis. In an attempt to reduce preventable harm to individuals with opioid use disorder (OUD), federal, state, and local governments have temporarily modified law and policy to increase access to OUD treatment and divert some individuals at high risk away from the correctional system. In this Commentary, we briefly describe how people with OUD are at increased risk for COVID-19, discuss existing policy barriers to evidence-based prevention and treatment for individuals with OUD, explain the temporary rollbacks of those barriers, and argue that these changes should be made permanent. We also suggest several additional steps that federal and state governments can urgently take to reduce barriers to care for individuals with OUD, both during the current crisis and beyond.